The Conquest of the School, a Review to Its Dramaturgy and Theatrical Experience From Popular Constitutionalism - Arcentales Illescas, Javier (Iuris Dictio, 2016)
This essay is part of the interdisciplinary studies that seek to relate Law and Literature and attempt to question legal thinking and work. It contains a reflexive exercise on popular constitutionalism theory departing from both the play La toma de la escuela written by French author HélÃ¨ne Cixous and the adaptation by Arístides Vargas, as well as its staging by Laboratorio Malayerba in Quito. My analysis aims at demonstrating that the characters of the play make an inquest into this legal theory possible, linking it to the Ecuadorian constitutional context as well as to the role of the subjects in the face of power.